Activity of Chymase, Tonin and Calpains in Rat Tissues Under Moderate Craniocerebral Hypothermia - Lomako, Viktoriia V.; Samokhina, Lyubov M. (Problems of Cryobiology and Cryomedicine, 2017)
The effect of moderate (32°C) craniocerebral hypothermia (CCH) on the activity of specific proteases such as chymase, tonin and calpains was studied. The proteases activity was determined in the blood serum, tissues of the central nervous system structures (cortex, hypothalamus, brain stem, cerebellum) and internal organs (heart, liver, lungs, kidneys) in animals. It has been revealed that the moderate CCH performed together with anesthesia promotes a sharp suppression of chymase and especially tonin activities (by 3-5 orders), accompanied with significant activation (in 10–50 times) of calpains. In comparison to the control the CCH led to more significant changes were found in hypothalamus, cerebellum and liver (for chymase), in the cerebellum and liver (for calpains), and if compared with the action of anesthesia the differences were present in the cerebellum, lungs, heart and kidneys (for tonin), in hypothalamus and cerebellum (for calpains). Probl Cryobiol Cryomed 2017; 27(3): 230–241